International Association for Pattern Recognition Workshop on Document Analysis Systems - Spitz, A. Lawrence; Dengel, Andreas (Series in machine perception and artificial intelligence, 2014)
""The 1st International Workshop on Document Analysis Systems (DAS94,) is a full workshop on research and development of systems for the analysis of document images. This volume will be of use to academic and industrial researchers, end-users, students and principal investigators."--Publisher's description